Bilateral Ureteral Triplication with Bilateral Complete Duplex Kidney: Surgical Challenges and Management via Laparoscopic Surgery (Bangladesh Journal of Endosurgery, 2014)
Bilateral ureteral triplication is a very rare form of congenital urinary tract anomaly;  so far, less than 10 cases have been reported worldwide. We report an infant  with bilateral complete duplex kidneys and a rare variant of Type II bilateral  ureteral triplication. The diagnostic challenges and successful laparoscopic  management are discussed.DOI: http://dx.doi.org/10.11593/bje.2013.0103.0021Bangladesh Journal of Endosurgery Vol.1(3) September 2013: 16-19